Contemporary Horror on Screen An Evolving Visual Narrative - Baker, Sarah; Rutherford, Amanda; Pamatatau, Richard (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book highlights how horror in film and television creates platforms to address distinct areas of modern-day concern. In examining the prevalence of dark tropes in contemporary horror films such as Get Out, Annabelle: Creation, A Quiet Place, Hereditary and The Nun, as well as series such as Stranger Things, American Horror Story and Game of Thrones, amongst numerous others, the authors contend that we are witnessing the emergence of a 'horror renaissance'. They posit that horror films or programmes, once widely considered to be a low form of popular culture entertainment, can contain deeper meanings or subtext and are increasingly covering serious subject matter. This book thus explores how horror is utilised as a tool to explore social and political anxieties of the cultural moment and is thus presented as a site for contestation, exploration and expansion to discuss present-day fears. It demonstrates how contemporary horror reflects the horror of modern-day life, be it political, biological, social or environmental. A vital contribution to studies of the horror genre in contemporary culture, and the effect it has on social anxieties in a threatening and seemingly apocalyptic time for the world, this is a vital text for students and researchers in popular culture, film, television and media studies.
Introduction -- Panic Watching: On the Function of Consuming Fictional Pandemics during a Real Pandemic -- When corporate biology gets caught up with Mother nature: An analysis of the Netflix viral horror The Rain -- Representations of environmental apocalyptic horror in Greenland -- From Haaa! To OOO: The New Cycle of Killer Objects: The New Cycle of Killer Objects -- Hereditary' s intergenerational curse -- Haunted Churches, Wicked Schools, Addressing Postcolonial History through Philippine Horror -- A Ghost Story and Micro-Cosmic Horror: Virginia Woolf's Indifferent Fear -- Shifting Subjectivities: Adopting the perspective of the Other in Mother and Get Out -- Pedophobiac Audiences: Mapping the presence of the child in horror cinema -- Good for Her; Ready or Not's Final Girl and the Rich, Patriarchal Family as Monster -- The It Duology: An Integrated Analysis of mainstream horror in the 2010s -- Why isn't There Anybody? Isolation and Loneliness in Kurosawa Kiyoshi's Pulse -- Paranormal Activity: The Marked Ones: A Failed Movie or a Movie Failed? -- The horror film and Donald trump: The revenge of minorities.
Keywords: Popular Culture; Culture -- Study and teaching; Motion pictures; Mass media and culture; Popular Culture; Cultural Theory; Film Studies; Global Film and TV; Media Culture